ISLAMIC RELIGIOUS EDUCATION IN THE FAMILY TO STRENGTHEN NATIONAL RESILIENCE OF SURAH AT-TAHRIM VERSE 6 PERSPECTIVE - Doli Witro (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2019)
Marriage is something sacred in human life, which aims to form a happy, safe, comfortable and full of harmony family between husband, wife, and children. It has become the nature of man to preserve and preserve something of value he possesses, moreover it is a part of him, namely children. In looking after and choosing children, one of the effective ways is to provide education. Education in the family not only begins when a child is born but since the child is in the womb, even when someone chooses a partner. The family is the first place for children to interact and learn. From the process of interaction, he gained many things that can shape his character and personality. In this case, the first education that must be taught to a child is Islamic religious education. The success or failure of Islamic education in the family has implications for national security. Because of the elements of the forming of the State, one of them is the population (society) consists of families. With the Islamic education that is taught, instilled in a family, it is hoped to be able to form a family that is safe, peaceful, comfortable, and devoted to Allah s.w.t. As contained in the Qur’an about the importance of caring for and family from hellfire by providing education to families in surah at-Tahrim verse 6. This paper will discuss some of the factors that describe and answer issues such as how is the education of Islam in the family perspective of surah at-Tahrim verse 6, how is the contextualization of Islamic religious education in the family, and how national resilience is based on family education. This is important to discuss because a weak child (knowledge and material) will be able to affect the harmony of a family. Then from a weak family can affect national security.Keywords:Islamic Religious Education, Family, National Resilience, Surah At-Tahrim Verse 6